Sensorineural Hearing Loss in Patients with Chronic Suppurative Otitis Media - Riaz, Fatima; Malik, Taimoor Lateef; Arif, Saira; Khattak, Shehrbano; Neelum; Riaz, Hamza (Indus Journal of Bioscience Research, 2025)
Background: Chronic suppurative otitis media is a common long-standing middle ear problem. It presents with persistent otorrhea through a perforated tympanic membrane for at least six to twelve weeks. Most patients develop conductive hearing loss. If the infection continues, inflammatory products can reach the cochlea and injure inner ear structures. This may lead to sensorineural loss that can become irreversible if ignored. Objective: To determine how often patients with chronic suppurative otitis media develop sensorineural hearing loss. Methods: A descriptive cross-sectional study was completed in the ENT unit of Mayo Hospital, King Edward Medical University, Lahore. The study ran from 16 May to 16 November 2024. One hundred fifty patients who fulfilled the inclusion criteria were selected. Age, gender, comorbid illness, and symptom duration were documented. Pure tone audiometry was done in all cases, and results were reported by an ENT consultant. Bone conduction thresholds at 500, 1000, 2000, and 4000 Hz were calculated in the diseased and opposite ear. Standard definitions were used to label sensorineural loss. All findings were entered on a structured proforma and analyzed with routine statistical tests. Results: The mean age was 36.9 ± 7.5 years. Symptoms continued for an average of 15.3 ± 3.3 weeks. There were 82 males, making up 54.7 percent of the group, and 68 females, making up 45.3 percent. Hypertension was present in 27 patients, while 24 had diabetes. Sensorineural loss appeared in 22 patients, which represented 14.7 percent of the total sample. Conclusion: A considerable number of patients with CSOM had sensorineural hearing loss in addition to conductive loss. Early diagnosis and complete hearing assessment are important to prevent permanent inner ear damage. Patient counseling and further research on prevention are recommended.